STRATEGI KEPALA SEKOLAH DALAM MEMBUDAYAKAN LITERASI DAN NUMERASI MELALUI PROGRAM KULINERS DI SMPN 3 SIDIKALANG - Yulira Putri Nirwana Boang Manalu; Harjito Harjito (Jurnal Manajemen Pendidikan, 2026)
This study aims to describe the principal's strategy in promoting literacy and numeracy through the KULINERS (Strong Literacy and Numeracy Tuesday) program at SMP Negeri 3 Sidikalang. This program emerged as a response to the low reading interest and numeracy achievement of students as shown in the Education Report Card. The principal acts as an instructional leader by initiating collaborative activities involving the entire school community.  The research uses a descriptive qualitative approach with data collection techniques through observation and in-depth interviews with the principal as the key informant. The data were analyzed using the Miles and Huberman interactive model. The results of the study revealed that: (1) the principal acted as an instructional leader who initiated a program based on an analysis of the Education Report Card data and the actual conditions of the students; (2) the implementation strategy combined a collaborative approach with all school stakeholders and a structured activity format that integrated academic and character building; (3) this program has a significant impact on increasing learning motivation, active student participation, and the formation of discipline and responsibility. The KULINERS program can increase learning motivation, literacy and numeracy skills, and positive character traits such as discipline, responsibility, and cooperation. This innovation is a good practice that can be replicated to support the School Literacy Movement (GLS) and the Pancasila Student Profile.